2018
DOI: 10.1111/imb.12372
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of reverse chemical ecology method: false positive binding of Aenasius bambawalei odorant binding protein 1 caused by uncertain binding mechanism

Abstract: Odorant binding proteins (OBPs) are considered as the core molecular targets in reverse chemical ecology, which is a convenient and efficient method by which to screen potential semiochemicals. Herein, we identified a classic OBP, AbamOBP1 from Aenasius bambawalei, which showed high mRNA expression in male antennae. Fluorescence competitive binding assay (FCBA) results demonstrated that AbamOBP1 has higher binding affinity with ligands at acid pH, suggesting the physiologically inconsistent binding affinity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 41 publications
(51 reference statements)
2
34
0
Order By: Relevance
“…It is persuasive that NlugCSP10 may contribute to the detection of cis ‐3‐hexenyl acetate communication. It has been reported that dsRNA treatment of Aenasius bambawalei also inhibited responses to volatiles (Li et al ., ), and similarly Dastarcus helophoroides was also non‐responsive to volatiles after dsRNA injection (Yang et al ., ). On the other hand, injection of dsNlugCSP10 did not show any effect on the behavioral responses of the BPH toward eicosane and (+)‐ β ‐pinene; it is likely that there are other CSPs and OBPs also participating in olfactory recognition in insects (Pelosi et al ., ; Zeng et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…It is persuasive that NlugCSP10 may contribute to the detection of cis ‐3‐hexenyl acetate communication. It has been reported that dsRNA treatment of Aenasius bambawalei also inhibited responses to volatiles (Li et al ., ), and similarly Dastarcus helophoroides was also non‐responsive to volatiles after dsRNA injection (Yang et al ., ). On the other hand, injection of dsNlugCSP10 did not show any effect on the behavioral responses of the BPH toward eicosane and (+)‐ β ‐pinene; it is likely that there are other CSPs and OBPs also participating in olfactory recognition in insects (Pelosi et al ., ; Zeng et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…The failure of adults displaying a preference for volatiles after RNAi treatment implies that disruption of olfaction caused by dsRNA prevented adults from detecting odors. It has been reported that dsRNA treatment of Aenasius bambawalei also inhibited responses to volatiles ( Li et al, 2018 ), and Dastarcus helophoroides was similarly non-responsive to volatiles after dsRNA injection ( Yang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent findings for the OBP1 of Aenasius bambawalei (AbamOBP1) report the binding of the protein with lower K D at acid pHs, inconsistent with the better binding at basic pHs in previous studies. The authors report that the binding stoichiometry between AbamOBP1 and tested ligands was not 1:1, which is likely caused by the presence of dimers or even trimers of OBPs and, therefore, a 100% active protein could not be assumed, suggesting false positives from the competitive binding assays (Li et al, 2018 ). It appears that a combined methodology such as fluorescence intrinsic quenching assays (Bette and Breer, 2002 ) could be in better accordance with behavioral assays.…”
Section: Insect Odorant-binding Proteins: Functional and Structural Fmentioning
confidence: 99%